Effect of sputter pressure on microstructure and properties of β-Ta thin films. (15th January 2020) - Ellis, Elizabeth A.I.; Chmielus, Markus; Han, Shangchen; Baker, Shefford P.
Abstract: Tantalum thin films may be deposited in two phases. The stable bulk alpha phase is well known, but the metastable tetragonal beta phase is relatively poorly understood. We reported previously on a series of 100% β -Ta films deposited under varying sputter pressures in a low-oxygen environment, and discussed texture, stresses, and phase selection. Here, we discuss microstructure, morphology, and properties of these same β -Ta films. Grain size increases with sputter pressure, which can be explained by the energies of incident species at the growing film. Mechanical properties were measured by nanoindentation. Hardness decreases with grain size in accordance with the Hall-Petch relation while comparison of indentation modulus with biaxial modulus measurements indicates that the β phase is elastically anisotropic, and much stiffer in the [001] direction than in others. Finally, a canonical resistivity value for virtually oxygen-free, 100% β -Ta films of 169 ± 5 µΩcm is reported for the first time. Graphical abstract: Image, graphical abstract